Can Bulgarian literature do well оn the German-speaking market? (Colloquia Comparativa Litterarum, 2025)
Due to the existence of an endless number of prejudices among Bulgarian intellectuals coupled with the paranoia that Bulgaria and its writers are being intentionally neglected by the world at large, the author of this article reveals the most influential factors that contribute to literary success, or failure thereof, among German-speaking readers and literary critics. He concludes that contemporary Bulgarian writers are inclined to either follow the Anglo-American pattern of fiction writing, or focus on their domestic cultural tradition, thus paying no attention to the universal human qualities and patterns of behaviour that would enable readers all over the world to indetify with their works. Toward its end, the paper points out a few specifics of Milena Kirova’s History of Bulgarian literature that have rendered the volume (in its German translation) valuable to the German-speaking audience.
Keywords: contemporary Bulgarian writers; German-language book market; cultural traditon; literary success